2004
DOI: 10.1111/j.1365-2036.2004.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture risk of women with primary biliary cirrhosis: no increase compared with general population controls

Abstract: Summary Aim : Patients with primary biliary cirrhosis may be at increased risk of osteoporosis but to what extent this is reflected in an increased fracture risk is unknown. We have enquired about the fracture experience of female primary biliary cirrhosis patients compared with sex‐ and age‐matched controls. Methods : Patients aged 30–75 with primary biliary cirrhosis and age‐matched controls were sent a postal questionnaire asking about their fracture history and details of risk factors for osteoporosis. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
0
20
1
Order By: Relevance
“…Six studies estimated the association between LC and any fracture risk . As shown in Figure , the pooled OR was 1.94 (95% CI, 1.59‐2.37) with a high heterogeneity ( I 2 = 88.4%, P < .001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies estimated the association between LC and any fracture risk . As shown in Figure , the pooled OR was 1.94 (95% CI, 1.59‐2.37) with a high heterogeneity ( I 2 = 88.4%, P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…Using this searching strategy, 2206 citations were retrieved, of which 32 articles were assessed in full-text format. Eventually, 8 of these were identified, 6,7,[11][12][13][14][15][16] which were composed of 5 cohort and 3 case-control studies, including 321 035 subjects and 31 272 fracture cases. The characteristics of each study are shown in Table 1.…”
Section: Literature Search and Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A two-fold increase in risk of the overall fracture of bones and fracture of the proximal femur and the forearm was observed in a group of 930 patients with primary biliary cirrhosis, in comparison to the general population (n = 9.202) [16]. Low-energy fractures occur in 14-21% of patients with chronic hepatitis and patients with liver cirrhosis and 45% in patients with end-stage liver failure referred for liver transplant [17]. Osteoporosis occurred in 36.6% and osteopenia in 48.1% of a group of 243 patients with chronic liver disease in the preparatory period for liver transplant [18].…”
Section: Osteoporosis In Liver Diseasesmentioning
confidence: 99%